2018
DOI: 10.21053/ceo.2018.00031
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Benefit of Silicone Intubation in Endoscopic Dacryocystorhinostomy

Abstract: ObjectivesInsertion of a silicone stent during endoscopic dacryocystorhinostomy (DCR) is the most common procedure to prevent rhinostomy closure. It has been claimed that silicone intubation improves the surgical outcomes of endoscopic DCR. However, many reports have documented an equally high success rate for surgery without silicone intubation. Accordingly, we conducted a systematic review and meta-analysis to clarify the outcomes of endoscopic DCR with and without silicone intubation and determine whether s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 37 publications
(38 reference statements)
0
46
1
Order By: Relevance
“…65,66 In general, even with such colonisation, silicone stenting paradoxically seems to increase success rates in both END-DCR, with no significant difference compared to the control group and EXT-DCR. 63,[67][68][69][70] However, as suggested by Murphy et al, if lacrimal stents are left in place for long periods, the resulting biofilms can interfere with the post-operative healing process and final success rates. 71 Given the potential influence of granulation tissue on the neo-rhinostomy, both with and without the application of silicone stents, even if it has not been demonstrated that ocular steroid application is useful in achieving higher success rates after END-DCR or EXT-DCT, steroid eye drops are generally considered the mainstay of post-operative treatment since they act as an antiinflammatory agent and prevent early closure of the neo-rhinostomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…65,66 In general, even with such colonisation, silicone stenting paradoxically seems to increase success rates in both END-DCR, with no significant difference compared to the control group and EXT-DCR. 63,[67][68][69][70] However, as suggested by Murphy et al, if lacrimal stents are left in place for long periods, the resulting biofilms can interfere with the post-operative healing process and final success rates. 71 Given the potential influence of granulation tissue on the neo-rhinostomy, both with and without the application of silicone stents, even if it has not been demonstrated that ocular steroid application is useful in achieving higher success rates after END-DCR or EXT-DCT, steroid eye drops are generally considered the mainstay of post-operative treatment since they act as an antiinflammatory agent and prevent early closure of the neo-rhinostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Its application is a controversial topic in the literature since some authors have reported its benefit in delaying fibrous closure and maintaining the patency of the neo-rhinostomy, while others report that the device predisposes to tissue granulation, adhesions and infections. 63,64 In fact, silicone tubes, by acting as a foreign body, can cause local inflammation and microorganism colonisation, which has been reported to be present in 94.7% of EXT-DCR and END-DCR, but is not sufficient to cause a clinical infection. 65,66 In general, even with such colonisation, silicone stenting paradoxically seems to increase success rates in both END-DCR, with no significant difference compared to the control group and EXT-DCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors sustain that silicone tubing may improve surgical outcomes by maintaining the patency of the lacrimal system 27,28 . At the same time, multiple systematic reviews and meta‐analyses have not demonstrated any additional advantages in silicone device placement, especially in endoscopic procedures 29,30 . A silicone stent may act as foreign inorganic material, leading to granulation with subsequent closure of the rhinostomy 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Three additional meta-analyses have since been published; 2 in 2018 by Kang et al 45 and Kim et al 46 with a third published in 2020 by Orsolini et al 47 All 3 studies included the same 9 RCTs, [48][49][50][51][52][53][54][55][56] while Kang et al 45 and Orsolini et al 47 both also included 2 additional RCTs. 57,58 Both of the studies, by Kim et al 46 (odds ratio [OR] 1.45; 95% CI, 0.77 to 2.73) and Kang et al 45 (OR 1.38; 95% CI, 0.89 to 2.12), concluded that there was no statistically significant difference in success rates. The Orsolini et al 47 study found that stent use favored greater success rates (OR 1.62; 95% CI, 1.01 to 2.59); however, given the wide CI and closeness to the null line (1.01), the recommendation for stent usage was weak overall.…”
Section: Stentingmentioning
confidence: 99%